Characteristics of the vowel system of the Standard Portuguese spoken in Angola - Undolo, Márcio (Revista de Filología Románica, 2015)
This article relates to specific areas of Phonetics and Phonology. It is intended, in effect, to highlight some characteristics of the educated spoken Portuguese in Angola, identified and collected from oral speeches of Angolan citizens and residents in Angola, students and professionals with medium-high level of scholarship. The speech of these individuals contains certain elements that differ from the linguistic norm at use in European Portuguese, recommended as the usage in Angola. At least with respect to the vowel system, it is shown that the vowel system of these individuals differs from the European Portuguese.
Keywords: vowels system; Standard Portuguese; Angolan Portuguese; standard